Da burocracia para a profecia: mudanças no neopentecostalismo brasileiro - Nunes, Éber (2008)
The new Pentecostalism calls attention because of its growing here in Brazil. Between the new Pentecostal churches can be mentioned the World s Church of God s Power . Founded by apostle Valdemiro Santiago in the year 1998, have conquered place in media and in number of adepts. The World s Church of God s Power is a dissident of Universal Church of God s Kingdom . Our research verify the differences and similarities between the World s Church of God s Power and Universal Church of God s Kingdom . To understand the phenomenological process, we choose the Weberian method of the sociology of comprehension. We built through the relive, one concept of pure and ideal type in the dialectic movement between World s Church of God s Power and Universal Church of God s Kingdom . In the ideality field, the Universal represents the bureaucracy, which is the process of institutionalization, historic results of all the religious movement. The World s Church of God s Power represents the prophecy, that the characteristic is the contestation. An exam of the rational domination and charismatic domination will help us to comprehend the phenomenon. The fundamental difference between the two churches is focused in charisma. The Universal institutionalize itself trough the bureaucracy, rational domination, and the World s is the prophecy that is reaffirmed by the charismatic domination.